Do quilombo à universidade: trajetórias, relatos, representações e desafios de estudantes quilombolas da Universidade Federal do Pará-Campus Belém quanto à permanência - CAMPOS, Laís Rodrigues (Universidade Federal do Pará, 2017)
This research presents an analysis of the trajectories, representations and challenges of Quilombola students admitted through the special selection of quota systems in undergraduate courses at the Federal University of Pará, focusing on their access and permanence in higher education. The study discusses the context of affirmative action in Brazilian higher education to Quilombola students. Thus, we focused on the experience of the Federal University of Pará, which adopted this type of policy in 2012. For this study, we began with a literature review about the subject and documentary surveys. We made a field research in Belém Campus of UFPA to collect documental sources. We interviewed five university Quilombola students who entered in the university from 2013 to 2015,in order to obtain reports about their life experiences since their lives in the Quilombo until their entrance and permanence in the university. The sample of these data collection revealed that the entry into the university was a great achievement to Quilombola population. But they still face many challenges to remain at the University such as prejudice and / or institutional racism, lack of academic activities that address the quilombo reality, difficulties about the capital information in the university area, due to this context the quilombola students organized a collective to fight for the recognition of their rights in the university.